Research progress of natural product-based nanomaterials for the treatment of inflammation-related diseases - Fan Cao; Si-Yu Gui; Xiang Gao; Wei Zhang; Zi-Yue Fu; Li-Ming Tao; Zheng-Xuan Jiang; Xulin Chen; Haisheng Qian; Xianwen Wang (Materials & Design, 2022)
Inflammatory diseases present with dysregulated inflammatory reactions and oxidative stress, resulting in heavy health-associated economic burden to society. Current mainstream therapies, including traditional therapies such as steroids, non-steroidal anti-inflammatory drugs (NSAIDs) and immunosuppressants, as well as novel biological strategies such as cytokine and intracellular signal inhibitors, cannot cure inflammatory diseases and always cause a series of unexpected adverse effects. Natural products (NPs), which are complex chemical molecules with abundant biological activities derived from microorganisms and plants, have demonstrated great potential for treating inflammatory diseases with several unresolved drawbacks. Increasing studies have indicated that NP-based nanomedicine resulting from the combination of NPs and nanotechnology may open a brand-new vista for the therapy of inflammatory diseases. In the present review, we summarize the classification of NP-based nanomedicine and its potential therapeutic effects in various inflammatory diseases, as well as further elucidate the challenges in the wide clinical application of NP-based nanomedicine to promote a comprehensive understanding and development of inflammatory disease therapy by NP-based nanomedicine.